Obstetric emergencies: preparedness among nurses for safe motherhood - Verma, Shraddha; Jain, Manisha; Budhwani, Chhaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Obstetric emergencies may turn catastrophic in women’s as well as obstetrician’s life. In the event of real emergency, all prior preparations may fall deficient. Every little contribution towards safe confinement brings about large reductions in maternal mortality and morbidity. Methods: Cross-sectional questionnaire based study carried out on nurses involved in perinatal care of parturient conducted at the Dept of Obstetrics & Gynecology of PCMS & RC, Bhopal. Results: Total study participants were 36 (100% response rate). Majority (83%) were aware about the two leading causes of maternal mortality (PE, PPH). Twenty four (67%) knew the warning signs of eclampsia and 61% knew the signs of eclampsia but only 17% were aware of MgSO4 toxicity. Only 56% could correctly prepare the loading dose of MgSO4. All were aware about PPH; however only17% knew methergine as the drug for active management. Grossly wrong attitude noted only in 27% for PPH and 27% for severe PE. Overall preparedness for emergency was satisfactory in LR and PNC. Conclusions: Though the overall awareness for identifying emergencies (PE, PPH) was satisfactory, lacunae in awareness were noted about components of eclampsia, magnesium toxicity and drugs required for initial management of PE and PPH. Preparedness of nurses in labour room and postnatal ward was fairly good. Regular assessment of awareness & preparedness for obstetric emergencies would be desirable to optimize the overall delivery outcomes especially at peripheral rural centres where nurses are primarily involved in the care of labouring women.